Bargaining Game And Equity Sharing System In Employment Problem. - Kamil, Anton Abdulbasah (2005)
Profit sharing has been proposed as a solution to underemployment resulting from collective bargaining, but the empirical result are ambiguous and the theoretical basis for this claim is weak.